Legal control of waste disposal in Malaysia / Ahmad Hawari Saffini, Lukman Hakim Zainurin and Alkamil Kamarudin - Saffini, Ahmad Hawari; Zainurin, Lukman Hakim; Kamarudin, Alkamil (2012)
The issue of waste disposal in Malaysia is a never-ending story. Although all of these wastes were collected regularly around housing area by environmental agencies, it does not put a stop to those wastes. All of them will be dumped at the dumping site nearby and every day Malaysia produces thousand kilograms of waste. Factories and industries also contributed to the alarming amounts of waste produced. They produced industrial waste, in which to some extent, hazardous and can cause health diseases. Most of the modern industries produced hazardous by-products which can dissolve easily into underground water that connects directly to Malaysian rivers. Currently, Environmental Quality Act 1974 is the nearest legislation that deals with waste disposal. However, this act is not discussing about waste management and disposal completely. In fact, the act only involves of 51 sections to regulate all effluents and wastes produced all around Malaysia. Moreover, the thin line that distinguishes separation of power between Federal Government and State Government in handling environmental issues is yet to be drawn. Furthermore, the enforcement power seems to be inadequate to covers all industrial and domestic waste producers. In response to this problem, we propose to study on the legal control of waste disposal in Malaysia, whether the laws need to be improvised, whether extra enforcement force needed to ensure the law stands or whether Malaysia already has the best environmental policy in the region. Apart from that, we also will study and comparing the waste disposal system and policies of another developed and developing countries from all around the world.